(untitled) (Journal of Accessibility and Design for All, 2016)
This article discusses the design of data collection instruments that include the opinions of blind students, in accordance with the principles of Universal Design (UD). The aim of this study is to understand the importance of adapting data collection instruments for the inclusion of disabled persons in field research in Architecture and Design, among other fields. The data collection instruments developed were a play interview with a tactile map and a 3D survey with the use of tactile models. These instruments sought to assess the school environment experienced by blind students. The study involved students from the early years of a school for the blind who had not yet mastered the Braille system. The participation of these students was evaluated. A multidisciplinary team consisting of architects, designers, educators, and psychologists lent support to the study. The results showed that the data collection instruments adapted to blind students were successful in making the group of authors examine questions regarding UD. An analysis of the participatory phase showed that the limitations resulting from blindness determine the specificities in the adaptation and implementation process of the instruments in schools. Practical recommendations for future studies related to instruments in the UD thematic are presented. This approach is in line with the global trend of including disabled persons in society based on these users’ opinions concerning what was designed by architects and designers.